Deciduoma, a Large Intrauterine Mass of Deciduosis - Megha Dasani; Hwa Jeong Lee; Asha Rijhsinghani (Thieme Medical Publishers, Inc., 2019)
Deciduosis is the presence of ectopic decidual tissue outside the uterus, pelvic, or abdominal organs usually associated with pregnancy. It usually presents as smaller lesions but can be larger vascular lesions. Typically, these masses are detected incidentally during operative procedures. Our patient was referred at 14 weeks for a large intrauterine mass detected on ultrasound examination that was initially thought to be an acardiac twin. The mass was highly vascularized. However, since the patient was asymptomatic, she strongly desired to continue the pregnancy. The pregnancy was followed closely from 14 to 39 weeks with serial ultrasound examinations. The vascularity was documented to diminish overtime and the mass appeared to convolute as well. Due to the decrease in vascularity of the mass, the patient was allowed spontaneous vaginal delivery at term. Following delivery of the fetus and the placenta, the mass was easily extracted manually without any complications.